Production of monoclonal antibody to quantify serum CA125 concentration in breast and ovarian cancer patients - Xuan, Nguyen Thi; Ha, Nguyen Trong (Academia Journal of Biology, 2020)
Ovarian carcinoma (OC) and breast cancer (BC) are mainly caused by alterations in genes such as BRCA1 and BRCA2, which are involved in differentiation and survival of cancer cells. The protein CA125 (MUC16) is released by cancer cells in most OC and a few BC patients. The cut-off point of CA125 level for tumor growth and metastasis is 35 U/mL. Production of CA125 monoclonal antidody (mAb) to determine expression level of this antigen by ELISA has been well known. In this study, we aimed to generate CA125-specific mAb for developing a new in-house ELISA kit. To this end, BALB/c mice were immunized with CA125 protein and splenocytes of immunized mice were fused with myeloma Sp2/0 cells. Efficiency of mAbs secreted from the hybridoma clones was examined by ELISA and flow cytometry analysis. As a result, among 3 stable hybridoma cell lines identified, A1 clone attained about 90% positive for anti-CA125 mAb, whereas H1 and H3 clones were about 40% and 50% positive for anti-CA125 mAb, respectively. By flow cytometry analysis, anti-CA125 mAb from A1 clone was more specific to CA125 antigen present in OVCAR -3 cells than those from H1 or H3 clone. In addition, the isotype of the obtained mAb was specific IgG1 and Kappa light chain. In conclusion, the mouse anti-human CA125 mAb generated in our lab was specifically binding to CA125 antigen and used as the capture antibody in sandwich ELISA system for early diagnosis as well as monitoring therapeutic response in OC patients.